Suicide attempt by hanging - A study on patients admitted in tertiary care hospital in Eastern India - Manoj Kumar Sahoo; Harshita Biswas (Wolters Kluwer Medknow Publications, 2024)
Background: Suicide is defined as a fatal self-injurious act with some evidence of intent to die. Despite the evolution of sophisticated methods to commit suicide, hanging remains one of the commonest methods to commit suicide across the world. To evaluate the individuals using hanging as a method of suicide and identify the contributing factors for this behaviour. Material and Methods: The study was carried out in a tertiary care hospital, over a period of 1 year on the suicide attempters using the method of hanging. Semi-structured in-depth interviews were conducted with all the 46 attempters. The questions focused on the precipitating events present before the attempt. After the in interview the risk factors of the conversations were identified, tabulated and categorized using descriptive analysis. Results: Findings from descriptive analysis reveals that significant age group using this method was below 19 years followed by 20-29 age group, female attempters were more compared to male. Psychiatric diagnosis was present in 8 attempters and 4 attempters had alcohol/substance dependence. The most common personality component in attempters was impulsivity. The most common immediate stressor found were financial stress, conflict with family, spouse, humiliation, substance abuse, exam stress and domestic violence. Conclusion: This study demonstrates that the reasons for suicide attempt by hanging is multifactorial. which includes, psychiatric diagnosis, personality factors, immediate stressors, ease of use, and accessibility, Overall, our study adds to understanding the intricates of this method and will help in developing effective suicide prevention strategies.